Metaphilosophy and Argument: The Case of the Justification of Abduction - Olmos, Paula (Informal Logic)

(untitled) (Informal Logic, 2021)
This paper is an essay on metaphilosophy that reviews, describes, categorises, and discusses different ways philosophers have approached the justification of abduction as a mode of reasoning and arguing. Advocating an argumentative approach to abduction, I model the philosophical debate over its justification as the critical assessment of a warrant-establishing argument allowing “H explains D” to be used as a reason for “H can be inferred from D.” Philosophers have discussed the conditions under which such kind of generic argument can be accepted, and I identify five kinds of such conditions, namely: a) dialectical/procedural restriction; b) claim restriction; c) restriction over acceptable explanatory principles; d) balancing restriction; and e) epistemic restriction.